Homosocial Bonds and Narrative Strategies in Adolphe Belot’s Mademoiselle Giraud, ma femme (1870) - Janicka, Iwona (Romanica Silesiana)
Adolphe Belot’s bestseller Mademoiselle Giraud, ma femme (1870) is a striking example of narratological tension between implied readers and the narrator. Adrien’s narrative, recounting the story of his unhappy marriage to a lesbian Paule Giraud, is significantly influenced by homosocial bonds with the male reading public — the implied readers of the text. Conscious of clear expectations towards a heterosexual man and a husband, the narrator reverts to hyperheterosexual narration in order to give legitimacy to his story and his desires. However, his narrative strategies backfire on him and, in consequence, undermine his credibility. The paper shows how tension in the choice of narrative tools subverts the blatantly anti-lesbian message of the text. By using René Girard’s theory of triangular desire and mimesis, the article also proves that the narrator is a male lesbian who had to subscribe to 19th-century convention of a husband. Key words: 19th-century literature, French literature, queer studies, male lesbianism, lesbian, narratology, René Girard, mimesis, triangular desire, Adolphe Belot, implied reader, homosocial bonds, manipulation.